Modernization tradition and identity : the Kompilasi Hukum Islam and legal practice in the Indonesian religious courts - Nurlaelawati, Euis (ICAS publication series. Monographs, 2010)
This book discusses the legal attitude of judges in Indonesian Islamic courts after a codified legal code was issued in the form of the Kompilasi Hukum Islam.